E-learning user interface design for lecturers based on usability scale system approach (Case Study: E-Learning Universitas Muhammadiyah Magelang) - Iqbal Ridwan Darmawan; Purwono Hendradi; Pristi Sukmasetya (Borobudur Informatics Review, 2022)
Universitas Muhammadiyah Magelang provides an online learning service portal through an e-learning website MOCA. However, the low level of use of the MOCA website and the usability problems that usually arise in MOCA, indicate the need for usability testing. Usability testing is carried out to measure usability aspects, namely: effectiveness, efficiency, and user satisfaction. This study used a System Usability Scale questionnaire which was tested on 61 lecturers. This study aims to measure usability aspects according to the user's subjective assessment. The results of the study can describe the level of usability of MOCA from the user's point of view. the results of the MOCA usability test using the SUS method got a score of "64" and this figure is still below the average (below average) of 68. For acceptable ranges, it shows that the current MOCA is in a "marginal (high)" position, for the grade scale gets a “D” predicate, and for adjective ratings it can be said to be “OK” and that means the current MOCA quality score is acceptable but needs a lot of improvement. In addition, this study provides recommendations in the form of a prototype designed based on suggestions from respondents and then tested based on the heuristic aspects of the relevant journal. The prototype design that has been designed is tested on 5 respondents as evaluators. The results of the heuristic test obtained were "4.32" which means 5 respondents were "satisfied" with the prototype user interface design proposed by the researcher.